PENGARUH PERSEPSI PEMILIK DAN PENGETAHUAN AKUNTANSI PELAKU USAHA MIKRO KECIL DAN MENENGAH TERHADAP PENGGUNAAN INFORMASI AKUNTANSI: Studi Kasus Pada UMKM Jagung Goreng Air Panas Semurup - Rio Baviga (Gapenas Publisher, 2022)
The problem raised in this study is the Perception and Knowledge of UMKM owners in Kerinci Regency on Accounting Information. This research was conducted on Fried Corn UMKM in Semurup Hot Water Village. Based on the results of the study, there is no effect of the perception of UMKM actors on the use of accounting information, this is evidenced by the perception t value is smaller than t table (1.197 < 2.073) and a significance value of 0.244 which means it is greater than 0.05 (0.244 > 0, 05), while there is an effect of accounting knowledge on the use of accounting information with t table (2.896 > 2.073) and the significance value is less than 0.05 (0.008 <0.05). And there is a simultaneous effect of perception and knowledge of accounting on the use of information. This is evidenced by Fcount > Ftable, 4,540 > 3.44 and the magnitude of the influence given by the variable of perception and accounting knowledge on the use of accounting information at UMKM Fried Corn in Air Panas Semurup Village is only 22.8% while 77.2% is influenced by other factors not investigated in this study